Identifikasi Timbulan dan Komposisi sampah di Kecamatan Bojongkaler Kota Bandung - Kurniasari, Opy (Bumi Lestari, 2025)
Abstract Waste is still a major problem that has not been completely resolved. There are many obstacles in waste management, one of which is the condition of waste from the community that is still mixed, making it difficult to implement processing methods. The aim of this study is to identify waste generation and composition in the Bojongloa Kaler Subdistrict as an initial step to provide comprehensive data in designing an effective waste management system. Considering the high population density, this location was chosen as the initial research site.. The research method begins with selecting sub-districts for the study area, using parameters on the scale of determining the importance of service areas as outlined in SNI 8632:2018. Waste sampling was conducted for 8 consecutive days based on SNI 19-3964 1994. based on high, medium, and low economic income levels. The sampling results show that the household waste generation in Kopo, Jamika, and Babakan Tarogong sub-districts, in terms of weight per capita per day, is 0.2 kg/person/day, 0.3 kg/person/day, and 0.3 kg/person/day respectively. The predominant composition of household waste in Kopo, Jamika, and Babakan Tarogong sub-districts is kitchen waste (food waste), at 49.26%, 45.07%, and 44.35% respectively. The second most common type of waste in Kopo and Babakan Tarogong sub-districts is plastic, accounting for 28.57% and 32.44% respectively. In contrast, in Jamika sub-districts, the second most common waste is categorized as others, while plastic ranks third at 16.10%. Keywords : Household waste, waste generation, waste composition, kitchen waste, plastic waste